Adult Food Insecurity is Associated with Heavier Weight Preferences among Black Women - Layton Reesor-Oyer; Nadia Garcia Marroquin; Daphne C. Hernandez (New Prairie Press, 2019)
Food insecurity is related to overweight/obesity among women. However, it is unknown whether food insecurity impacts individuals' desired body composition, and whether this relationship differs by race/ethnicity similar to perceived ideal weight status. This study aims to evaluate whether food insecurity is related to elevated preferred weight status (e.g., overweight/obese versus normal weight) among black, white, and Hispanic women classified as overweight/obese. Four waves of NHANES data (2007-2014) were merged and yielded a total of 907 black, 1,271 white, and 1,005 Hispanic non-pregnant adult (age 20 to 59) women classified as overweight/obese. Participants self-reported their preferred weight status, adult-level food security, and demographic covariates. Covariate-adjusted logistic regression models stratified by race/ethnicity evaluated the role of food insecurity related to preferred weight status. Among black women, those who were food insecure were at 51% increased odds of preferring an overweight/obese weight status (OR: 1.51; 95% CI: 1.08 - 2.13; p = .02) relative to their food secure counterparts. Among white and Hispanic women, those who were food insecure had similar odds of preferring an overweight/obese weight status (White: OR: 1.07; 95% CI: 0.68 - 1.71; p = .76; Hispanic: OR: 0.95; 95% CI: 0.66 - 1.37; <p = .77) relative to their food secure counterparts. Food insecurity results in the desire to be heavier among black women classified as overweight/obese. However, it does not impact white and Hispanic women classified as overweight/obese. Practitioners must consider weight preferences prior to providing obesity prevention information, particularly among food insecure black women.